Risk and burden of low birthweight related to maternal PM2.5 exposure in Iran: A national causal inference study - Ziqing Tang; Xuan Long; Kai Wang; Klaus Berger; Yunquan Zhang; Fatemeh Mayvaneh (Ecotoxicology and Environmental Safety)
Background: Maternal ambient fine particulate matter (PM2.5) has been linked with fetal low birthweight (LBW), while national causal evidence is limited, particularly in low- and middle-income countries. Methods: We used nationwide registry-based birth records of 3839531 singleton livebirths, with maternal age (MA) between 15 and 49 years, across 31 provinces in Iran from 2013 through 2018. Monthly gridded concentrations of ambient PM2.5 during entire pregnancy were estimated through validated spatiotemporal models. We adopted traditional logistic/linear regression and double robust model (DRM) based on generalized propensity scores (GPS) to evaluate associations of maternal PM2.5 exposure with LBW risk and birthweight change. MA-specific exposure-response functions were investigated using restricted cubic splines in both traditional and casual inference models. PM2.5-attributable LBW burden were parallelly estimated, under the scenarios of achieving counterfactual exposure levels of multiple WHO interim targets. Results: A total of 228655 LBW births were identified, and mean birthweight of was 3187 g. Both traditional and causal modelling approaches yielded consistently positive associations of maternal PM2.5 exposure with increased LBW risk and reduced birthweight, but marginally larger effect estimates were seen under GPS-based DRM analyses. Specifically, a 10-μg/m3 increase in ambient PM2.5 during the entire pregnancy was associated with the odds of 1.071 (95% confidence interval: 1.066, 1.076) for LBW and reduced birthweight of 8.9 (8.4, 9.4) g in GPS-based DRM analysis. MA-stratified analyses suggested non-linear exposure-response relationships of PM2.5 exposure with both LBW (Pnonlinear <0.001) risk and birthweight change (Pnonlinear <0.001) over the exposure range of 17–104 μg/m3, with notably steeper slopes at low concentrations (<37.3 μg/m3). According to GPS-based DRM analysis, achieving the interim target level 1–3 of annual PM2.5 (i.e., 35, 25, and 15 μg/m3) could avoid 5.5%–32.6% of overall LBW infants and birthweight loss of 7.0–57.6 g per livebirth during 2013–2018 in Iran. Conclusions: Our findings provided nationwide evidence of causality for elevated LBW risk and birthweight loss associated with maternal PM2.5 exposure in Iran. Improving air quality through multisectoral efforts may avoid dramatic LBW burden to promote neonatal health later in life.